2005
DOI: 10.1093/humrep/deh654
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic studies in two human reciprocal translocations and their association with spermatogenic failure

Abstract: By comparing these two different translocation carriers with different fertility outcomes, we discuss the possible mechanisms by which translocations might cause the spermatogenesis process to fail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 26 publications
5
50
0
2
Order By: Relevance
“…Previous observations have also suggested that heterosynapsis between the free arms of trivalents and quadrivalents inhibits the association of these multivalents with the XY body reviewed in Solari, 1999). Recent observations on two human reciprocal translocations showing very different frequencies of heterosynapsis give further support to this suggestion (Oliver-Bonet et al, 2005b). The present results agree with these previous observations, as it is shown that no heterosynapsed arms of cases 1 and 3 are ever found associated with the XY body.…”
Section: Discussionsupporting
confidence: 93%
“…Previous observations have also suggested that heterosynapsis between the free arms of trivalents and quadrivalents inhibits the association of these multivalents with the XY body reviewed in Solari, 1999). Recent observations on two human reciprocal translocations showing very different frequencies of heterosynapsis give further support to this suggestion (Oliver-Bonet et al, 2005b). The present results agree with these previous observations, as it is shown that no heterosynapsed arms of cases 1 and 3 are ever found associated with the XY body.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have shown normal timing and progression of condensation through the pachytene stage for the sex body in a carrier of a t(Y;1) translocation (Sun et al, unpublished results) and for the sex body associated with the quadrivalent in a t(13;20) carrier (Oliver-Bonet et al, 2005). These results, together with the fact that there is a strong relationship between SB inactivation and XY condensation (Fernandez-Capetillo et al, 2003), do not support the model of gene activation on the X chromosome.…”
Section: The Sex Body Affairmentioning
confidence: 97%
“…In a recent analysis we have compared the meiotic process in two translocation carriers with different fertility outcomes, one normozoospermic and the other azoospermic (Oliver-Bonet et al, 2005). A significant number of quadrivalents were attached to the SB in the azoospermic carrier, whereas such an association was never detected in the normozoospermic carrier.…”
Section: Playing Catchmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In one study, at least two different meiotic checkpoints were present in a t (13;20) carrier; 22 in such a case, an association may occur between the sex body and quadrivalent structure, which could also increase during the pachytene stage, such that decreased numbers of cells reach the later pachytene …”
Section: Impact Of Chromosomal Translocations On Male Infertilitymentioning
confidence: 99%